Сравнительный анализ электрохимической активности порошков гидроксида никеля - Коток, В. А.; Кошель, Н. Д.; Гречанюк, А. А.; Костыря, М. В.; Кашеварова, Е. В. (НТУ "ХПИ", 2008)
У роботі розглянуті порівняльні кінетичні характеристики гидроксида нікелю як активної речовини лужних акумуляторів. Дані отримані методом прискореного імпульсного розряду. Метод розроблено для порівняння характеристик матеріалів, отриманих різними способами.

Comparative kinetic characteristics of nickel hydroxide as active substance of the alkaline accumulators have been examined during the investigation. The results have been received by a method of intensive pulse discharge. The said method was worked out for comparison of characteristics of materials received by various ways.
Keywords: ускоренный импульсный разряд; УИР; активное вещество; коэффициент диффузии; ток; поляризация; ГНЗ